Enhanced Field Effect Mobility on 4H-SiC by Oxidation at 1500°C - S. M. Thomas; Y. K. Sharma; M. A. Crouch; C. A. Fisher; A. Perez-Tomas; M. R. Jennings; P. A. Mawby (IEEE Journal of the Electron Devices Society, 2014)
A novel 1500°C gate oxidation process has been demonstrated on Si face of 4H-SiC. Lateral channel metal-oxide-semiconductor-field-effect-transistors (MOSFETs) fabricated using this process have a maximum field effect mobility of approximately 40 cm\2 V-1 s-1 without post oxidation passivation. This is substantially higher than other reports of MOSFETs with thermally grown oxides (typically grown at the standard silicon temperature range of 1100-1200°C). This result shows the potential of a high temperature oxidation step for reducing the channel resistance (thus the overall conduction loss), in power 4H-SiC MOSFETs.